The public boards as public administration (and citizens as administrative participants). - Nicoly John A.
Service on public boards is described in a normative model of public administration. Further, public boards, such as the historic architectural review boards discussed here, provide conique opportunites for students of government and public administration. The public board serves an importan balace within the local government. Public boards provides expertise not boards provide an important interface for citizens to their elected government and their career public administration; and public boards provide an improtant opportunity for citizens to involve themselves with their government. This citizen as administrative participant is not typically schooled in government or in public administration, but an opportu
Keywords: Public Board; Citizen Participation; Public Administration -- Citizen Participation